Une approche cognitive de la narrativité musicale - Christian Hauer (Cahiers de Narratologie)
This paper hypothesizes a cognitive approach of musical narrativity : from the cognitive angle, music is necessarily narrative. In this perspective, the paper discusses three main points. (1) Experienciality, in the meaning of « real life experience » through a consciousness, is, according to Fludernik, necessarily narrative. This concept is here applied to music. (2) In music, there is a narrator who tells the work, by a performance. He appears as the place of meaning. He is the concrete and essential presence so that there is music, or experienciality. (3) The embodied simulation (or empathy) appears like a cognitive phenomenon founding the musical and narrative experience of the listener, since it allows him to mimic physically the experienciality proposed by the narrator-performer. To address these points, this paper also approaches questions as essential as the mirror mechanism and thus reciprocal relationships between perception and action (see « inverse » and « forward models »), and the fictionality in music.